A Light‐Operated Molecular Cable Car for Gated Ion Transport. Issue 27 (6th May 2021) - Wang, Chenxi; Wang, Shunkang; Yang, Huiting; Xiang, Yanxin; Wang, Xuebin; Bao, Chunyan; Zhu, Linyong; Tian, He; Qu, Da‐Hui
Abstract: Inspired by the nontrivial and controlled movements of molecular machines, we report an azobenzene‐based molecular shuttle PR2, which can perform light‐gated ion transport across lipid membranes. The amphiphilicity and membrane‐spanning molecular length enable PR2 to insert into the bilayer membrane and efficiently transport K + (EC50 =4.1 μm ) through the thermally driven stochastic shuttle motion of the crown ether ring along the axle. The significant difference in shuttling rate between trans‐PR2 and cis‐PR2 induced by molecular isomerization enables a light‐gated ion transport, i.e., ON/OFF in situ regulation of transport activity and single‐channel current. This work represents an example of using a photoswitchable molecular machine to realize gated ion transport, which demonstrates the value of molecular machines functioning in biomembranes. Abstract : Inspired by natural rhodopsin, an azobenzene‐based molecular rotaxane was designed to insert into lipid membranes for the regulation of ion transport. Based on the shuttle transport mechanism, the significant difference in shuttling rate between trans ‐ and cis ‐isomer caused by molecular isomerization facilitates light‐gated ion transport.